2022
DOI: 10.3390/cryst12040527
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Thermoelectric Detection of Sigma Phase in 2507 Duplex Stainless Steel

Abstract: Duplex stainless steel has significantly broadened the range of applications of stainless steel. They have a dual-phase microstructure containing ferrite and austenite at approximately a 50–50% phase ratio. Their corrosion resistance is much better compared to the traditional austenitic stainless steel, especially in surroundings containing chloride ion. Moreover, the large stress yield of duplex steels offers significant advantages in structural applications. The ferrite phase in some duplex stainless steels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a very recent work [ 14 ], the influence of heat treatment and that of plastic deformation were investigated upon the appearance of the sigma phase in 2507 duplex stainless steel. In this study, only the thermoelectric power measurements and magnetic saturation polarization were applied to monitor the microstructural changes generated by cold rolling and heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent work [ 14 ], the influence of heat treatment and that of plastic deformation were investigated upon the appearance of the sigma phase in 2507 duplex stainless steel. In this study, only the thermoelectric power measurements and magnetic saturation polarization were applied to monitor the microstructural changes generated by cold rolling and heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Duplex stainless steels have great strength (yield strength, R p0.2 ≈ 500 MPa) and excellent corrosion resistance especially against stress corrosion [1][2][3][4][5]. Thus, the application of duplex stainless steels (DSSs) in civil engineering, chemical, oil and gas industries are constantly growing [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation behavior, influencing factors, and effects of the sigma phase on DSS have been widely studied. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Kazuhiro reported the effects of alloying elements on the precipitation of the sigma phase in SDSS. [26,27] The authors found that Cr and Mo, which are useful for improving the corrosion resistance, can promote sigma-phase precipitation, but the phase does not always grow rapidly.…”
mentioning
confidence: 99%